A Design Procedure and Control Method for Improving Efficiency of a Family of Resonant Converters Over Wide Operating Conditions - Jasem Shahsevani; Reza Beiranvand (IEEE Access)
Resonant converters are widely recognized as highly efficient converters. They find numerous applications in various industries such as electric vehicles, battery chargers, and photovoltaic cells. However, low efficiency under light-load or no-load conditions is one of their main challenges, which arises when their switching frequencies deviate significantly from their resonance frequencies during output voltage regulation, resulting in high circulating currents and switching harmonics values. Here, a novel design procedure and control method are proposed for the resonant converters, which have parallel components in their resonant tank circuits to address their light-load or no-load low-efficiency issues. This control algorithm is based on the frequency modulation method and utilizes a variable capacitor or inductor in the resonant tank circuit, simultaneously. By designing each converter to operate between its two open and short-circuit resonance frequencies, and regulating its output voltage by changing the voltage gain-frequency characteristics to operate near a resonance frequency, consistently circulating currents are well limited. To validate the given method, a 100-500 W LLC resonant converter with 180-220 V input voltage and 48 V output voltage has been designed, implemented, and tested under different conditions to demonstrate its good performance. Experimental results clearly show that its efficiency exceeds 96% under all operating conditions.